Utilization of Mao (Antidesma thwaitesianum Muell. Arg.) Pomace Meal to Substitute Rice Bran on Feed Utilization and Rumen Fermentation in Tropical Beef Cattle - Nirawan Gunun; Pichad Khejornsart; Sineenart Polyorach; Chatchai Kaewpila; Thachawech Kimprasit; Ittipol Sanjun; Anusorn Cherdthong; Metha Wanapat; Pongsatorn Gunun (Veterinary Sciences, 2022)
This experiment was conducted to investigate the effects of replacing rice bran with mao pomace meal on feed intake, digestibility, and rumen fermentation in beef cattle. Four crossbred (50% Brahman × 50% Thai native) beef cattle with an initial body weight of 195 ± 13 kg and 16 months of age were used in a 4 × 4 Latin square design. The dietary treatments included four levels of RB replacement with mao pomace meal at 0, 33, 67, and 100% in concentrate diets. Rice straw was used as a roughage source, fed ad libitum. Replacement of mao pomace meal with rice bran did not affect (p > 0.05) the intakes of concentrate, rice straw, and total dry matter intake. Ether extract intake decreased linearly when increasing the levels of mao pomace meal (p < 0.01). The experimental diets had no effect (p > 0.05) on the digestibility of fiber and crude protein, while dry matter, organic matter, and ether extract digestibility decreased linearly in the group of mao pomace meal replacing rice bran (p < 0.05). Increasing levels of mao pomace meal in concentrate diets did not alter rumen pH, ammonia−nitrogen, or total volatile fatty acid concentration (p > 0.05). The proportion of propionate increased linearly (p < 0.05), whereas acetate and the acetate to propionate ratio decreased linearly (p < 0.05) when replacing rice bran with mao pomace meal. Moreover, the proportion of propionate was greatest, while acetate was lowest when mao pomace meal was included at 100% in the concentrate diet. In conclusion, the replacement of rice bran with mao pomace meal in a diet could enhance the efficiency of rumen fermentation. Nonetheless, it reduced the digestion of nutrients in tropical beef cattle.
Keywords: Ruminant Nutrition and Digestive Physiology; Phytase and its Applications; Agriculture and Rural Development Research